The Analysis of Irrigation Water Excess Percentage in Subak Ho Watershed During the Rainy Season - Pangestu, Dian Dwi Cahyo; Tika, I Wayan; Gunadnya, I.B. Putu (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
The excess of water availability is caused by excessive water discharge during the rainy season, and it doesn’t distribute evenly between upstream and downstream, where upstream water availability tends to be oversupply and downstream is deficient. With such conditions, research is needed on excess irrigation water during the rainy season in order to perform an optimal water management in Ho Watershed. Research was conducted to determine the percentage of excess irrigation water available in each subak and determine irrigation water management techniques to be proportionate to each subak section. The acquisition of primary data is done by interview, observation, and measurement methods, while secondary data is obtained from (BMKG) Region III Denpasar. The data obtained was further analyzed with CROPWAT 8.0 to find the percentage of excess irrigation water that occurs during the rainy season and to determine the distribution portion of irrigation water. The results showed the percentage of excess irrigation water in the Ho watershed during the rainy season averaged 207,31%, middle 417,78%, downstream 239,05%. Water distribution management techniques in the upstream, middle, downstream during the rainy season so that the excess is proportional by changing the initial discharge in accordance with the approximation discharge.